The use of antipsychotics among people treated with medications for dementia in residential aged care facilities. (18th January 2016) - Shin, Hee-Young; Gadzhanova, Svetla; Roughead, Elizabeth E.; Ward, Michael B.; Pont, Lisa G.
ABSTRACT: Background: Antipsychotic agents have limited efficacy for Behavioral and Psychological Symptoms of Dementia (BPSD) and there are concerns about their safety. Despite this, they are frequently used for the management of BPSD. This study aimed to assess the use of antipsychotics among people on anti-dementia medicines in Australian residential aged care facilities. Methods: Data were obtained from an individual patient unit dose packaging database covering 40 residential aged care facilities in New South Wales, Australia. Residents supplied an anti-dementia medicine between July 2008 and June 2013 were included. Prevalence of concurrent antipsychotic use was established. Incident antipsychotic users between January 2009 and December 2011 were identified. We examined initial antipsychotic dose, maximum titrated doses, type and duration of antipsychotic use, and compared use with Australian guidelines. Results: There were 291 residents treated with anti-dementia medicines, 129 (44%) of whom received antipsychotics concomitantly with an anti-dementia medicine. Among the 59 incident antipsychotic users, risperidone (73%) was the most commonly used antipsychotic agent. Amongst the risperidone initiators, 43% of patients had initial doses greater than 0.5 mg/day and 6% of patients exceeded 2.0 mg/day for their maximum dose. 53% of concomitant users received daily treatment for greater than six months. Conclusions: Our study using records of individual patient unit dose supply, which represents the intended medication consumption schedule, shows high rates of concurrent use of antipsychotics and anti-dementia medicines and long durations of use. The use of antipsychotics in patients with dementia needs to be carefully monitored to improve patient outcomes.